Charter township municipal income Zipaquirá (2014)
The main objective of this document is to present how the Zipaquirá tax statute is designed, according to social and economic characteristics. Define legislation and administrative procedures current which regulate income and municipal revenues. Contains general rules about administration, fiscalization, control, settlement, collecting and recovery of municipal taxes, sanctions and procedures applied according current tax legislation.